L’uso del ‘bianco’ nel restauro architettonico a Roma nel XIX secolo - Muratore, Olivia (Opus Incertum, 2017)
The essay highlights how the debate on the approach to restoration interventions that is still currently ongoing, could already be recognised in the great restoration projects carried out in Rome in the first two decades of the 19th century, together with some of the maintenance practices undertaken throughout the whole century. Attention is especially placed on the external finishings of architectural structures, and in the practice of the so-called whitewashing of the facades during the 19th century. Although very commonly used for conservation and urban regeneration purposes, these practeces were strongly criticised and occasionally attacked by personalities of the field of restoration that were more sensitive to the importance of safeguarding the ’patina’ which time had left on the surface of architectural structures, and that would otherwise be inevitably lost. Some of today’s theoreticians of restoration find food for thought in those issues, which they continue to propose as an element for discussion amongst the various positions which see in the treatment of the surfaces of historical architecture a fertile ground for methodological debate.